How medical treatment affects mean platelet volume as a cardiovascular risk marker in polycystic ovary syndrome?. Issue 8 (December 2015) - Kabil Kucur, Suna; Gozukara, Ilay; Aksoy, Aysenur; Uludag, Eda U.; Keskin, Havva; Kamalak, Zeynep; Carlioglu, Ayse
Abstract : Polycystic ovary syndrome (PCOS) is a prevalent disease with many potential long-term metabolic and cardiovascular risks if not managed appropriately. Mean platelet volume (MPV) is a marker associated with adverse cardiovascular events. In this study, we aimed to investigate MPV levels under ethinyl estradiol/cyproterone acetate or metformin therapy for the previous 6 months in PCOS. A total of 114 individuals [metformin treatment ( n = 18), ethinyl estradiol/cyproterone acetate treatment ( n = 29), newly diagnosed PCOS patient with no treatment ( n = 35), and control group of eumenorrheic healthy individuals ( n = 32)] were included in the current study. Hematologic parameters other than MPV were similar in all groups. The MPV value was significantly higher in the newly diagnosed PCOS patients compared with the other three groups independent of age, BMI, and C-reactive protein level in multiple regression analysis ( P < 0.01). The MPV value of control group was comparable to the groups under ethinyl estradiol/cyproterone acetate or metformin therapy ( P = 1.0). There was no statistically significant difference in the white blood cell count among the groups. The MPV values were positively correlated with the homeostatic model assessment-insulin resistance and Ferriman–Gallwey Score ( P = 0.044, r = 0.261; P = 0.037, r = 0.229, respectively). Ethinyl estradiol/cyproterone acetate and metformin similarly appear to decrease MPV, a marker of cardiovascular risk. Therefore, a possible beneficial effect of ethinyl estradiol/cyproterone acetate and metformin on long-term cardiovascular morbidities in PCOS may be suggested.